[Sorting cascadura] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Sorting baskets of cascadura for the aquaculture project. Fishes were sorted according to size.
Cataloger's title
Keywords: Fishes -- Trinidad and Tobago; Pond aquaculture -- Trinidad and Tobago; Caroni (1975) Limited